High-strength long glass fiber reinforced polyamide composite material and preparation method thereof
By preparing graphene oxide masterbatches in polyamide resin and combining them with long glass fibers and other materials, the problem of poor graphene dispersion is solved, and the mechanical properties and electrical conductivity of long glass fiber reinforced polyamide composite materials are significantly improved, meeting higher market demand.
Patent Information
- Application Number
- CN202411286852.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-09-13
AI Technical Summary
In the prior art, graphene has poor dispersion in polyamide resin, which makes it unable to effectively exert its potential value, thereby limiting the mechanical properties and electrical conductivity of long glass fiber reinforced polyamide composite materials.
Graphene oxide masterbatches are formed by mixing graphene oxide with polyamide resin in a specific ratio and undergoing a ball milling process under a liquid nitrogen atmosphere. Then, the graphene oxide masterbatch was mixed with high-modulus alkali-free glass fiber, compatible agent, crosslinking agent, antioxidant and lubricant at high speed, and finally a high-strength long glass fiber reinforced polyamide composite material was prepared in a twin-screw extruder.
It effectively solves the dispersion problem of graphene in polyamide resin, improves the mechanical properties and electrical conductivity of composite materials, and meets higher market demand.
Smart Images

Figure QLYQS_1 
Figure BDA0005043329230000021 
Figure BDA0005043329230000041
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer composite materials, and specifically relates to a high-strength long glass fiber reinforced polyamide composite material and a preparation method thereof. Background Art
[0002] Polyamide has become one of the most commonly used engineering plastics due to its many advantages such as excellent fluidity, heat resistance, chemical corrosion resistance, self-lubricating properties, high mechanical properties, good processing properties, etc. It is widely used in the automotive, home appliances, electronic appliances, power tools, medical equipment, construction and other industries; in order to further improve its mechanical properties, heat resistance, fatigue resistance, creep resistance and other properties during the application process, it is usually chosen to be reinforced and filled with other reinforcing fillers such as glass fiber, which can also reduce material costs.
[0003] Due to the differences in processing methods and product characteristics, people in this technical field distinguish between long glass fiber and short glass fiber reinforced nylon materials. Among them, long glass fiber reinforced polyamide materials have higher strength, modulus, impact strength, fatigue resistance, creep resistance and other outstanding characteristics. In order to further improve the mechanical properties and other functionalities of long glass fiber reinforced polyamide materials, it is necessary to carry out synergistic enhancement and modification. Graphene materials, with their unique physical structure, can give long glass fiber reinforced polyamide materials better mechanical properties and electrical conductivity and other functionalities. However, due to its microstructure and other reasons, graphene is very easy to cause agglomeration and uneven dispersion, and its potential value cannot be exerted.
[0004] In view of this, a method is developed to effectively solve the graphene dispersion problem and applied to long glass fiber reinforced polyamide composites, which can greatly improve the mechanical properties of the composites and meet greater market demands. Summary of the invention
[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a high-strength long glass fiber reinforced polyamide composite material and a preparation method thereof, which solves the problems in the prior art.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A polyamide composite material comprises the following raw materials in parts by weight:
[0008]
[0009] The graphene oxide masterbatch is formed by cross-linking graphene oxide and attaching it to polyamide resin PA6.
[0010] Furthermore, the polyamide resin is one or more of the aliphatic polyamide resins PA6, PA46, PA56, PA66, PA11, PA12, PA610, PA1010, PA1012, PA612, and PA1212.
[0011] Furthermore, the single filament diameter of the high modulus alkali-free glass fiber is 15-20 um, and the linear density is 1200 tex, 2400 tex or 3600 tex.
[0012] Furthermore, the chain extender masterbatch is an epoxy chain extender.
[0013] Furthermore, the processing aid is at least one of an antioxidant, a weathering agent, a lubricant and a pigment.
[0014] Furthermore, the preparation steps of the graphene oxide masterbatch are as follows:
[0015] Step 1: Take polyamide PA6 resin and graphene oxide in a ratio of 3:1, mix them evenly, put them in a ball mill, and perform ball milling process on the two in a liquid nitrogen atmosphere to obtain a mixed powder;
[0016] Step 2: Mix the powder with the compatibilizer, cross-linking agent, antioxidant and lubricant in a ratio of 96:3:0.2:0.4:0.4, mix them evenly at high speed using a high-speed mixer, and extrude and granulate them in a twin-screw extruder to obtain graphene oxide masterbatch.
[0017] Furthermore, the graphene oxide particle size D50≤5um; the cross-linking agent is at least one of dipropylbenzene peroxide, di-tert-butyl peroxide and tert-butyl perbenzoate;
[0018] Furthermore, the compatibilizer is at least one of POE-g-MAH, SEBS-g-MAH, and PP-g-MAH; the antioxidant is a mixture of a main antioxidant and an auxiliary antioxidant in a ratio of 1 / 2, the main antioxidant is a hindered phenol antioxidant 1098, and the auxiliary antioxidant is a phosphite antioxidant 9228; the lubricant is one or more of OP wax, polyester wax, and ethylene-acrylic acid copolymer.
[0019] The above-mentioned method for preparing a polyamide composite material is characterized by comprising the following steps:
[0020] Add polyamide resin, high modulus alkali-free glass fiber, graphene oxide masterbatch, compatibilizer and other processing aids into a stirring pot and mix evenly, then place it at the discharge port of a twin-screw extruder, add the chain extender masterbatch from the side feeding port, and after the material is sheared and plasticized by the twin screw, it is injected into the LFT-G impregnation mold at a constant conveying rate. The high modulus alkali-free glass fiber passes through the surface coating resin from the impregnation mold, and is cooled in a water tank, air-dried, and pelletized to obtain a polyamide composite material.
[0021] The above-mentioned polyamide composite material is used in the preparation of automobile plastic parts.
[0022] Beneficial effects of the present invention:
[0023] 1. The present invention prepares a graphene oxide masterbatch in a specific manner, and performs blending modification on a polyamide resin to prepare a high-strength long glass fiber reinforced polyamide composite material, which not only solves the dispersion problem of graphene oxide in polyamide resin, but also, under the action of a cross-linking agent, cross-links the nylon molecular chain with the hydroxyl groups on the surface of graphene oxide, effectively grafting the nylon molecules onto the graphene oxide sheet. The synergistic reinforcement effect of graphene oxide and glass fiber greatly improves the mechanical properties of the long glass fiber reinforced polyamide composite material, and also gives the composite material good electrical conductivity.
[0024] 2. The present invention uses a chain extender in the preparation of polyamide materials. During the chain extension process, the molecular chains of the PA6 molecules grafted on the surface of graphene oxide gradually expand, the molecular weight increases, and the entanglement between the chains increases, so that the molecular chains and the glass fibers are more closely combined, so that the graphene oxide is evenly attached to the surface of the continuous glass fiber, further effectively improving the mechanical properties of the composite material.
[0025] 3. The process route adopted in this patent to solve the problems of graphene oxide dispersion has obvious advantages over the prior art of preparing GE / PA6 composite particles by in-situ polymerization. The in-situ polymerization for preparing GE / PA6 composite particles requires a high-temperature reactor, harsh reaction conditions, and a very complicated operation process. The present invention can prepare functionalized graphene oxide masterbatch using a twin-screw extruder, has a simple operation process, and has good practical application effects. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solution of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] A high-strength long glass fiber reinforced polyamide composite material, comprising the following raw materials in parts by weight:
[0028]
[0029] The polyamide resin is one or more of the aliphatic polyamide resins PA6, PA46, PA56, PA66, PA11, PA12, PA610, PA1010, PA1012, PA612, and PA1212.
[0030] The single filament diameter of the high modulus alkali-free glass fiber is 15-20 um, and the linear density is 1200 tex, 2400 tex or 3600 tex.
[0031] The chain extender masterbatch is an epoxy chain extender, specifically styrene-glycidyl methacrylate, and the base resin is PA6.
[0032] The processing aid is at least one of an antioxidant, a weathering agent, a lubricant and a pigment.
[0033] The graphene oxide masterbatch is formed by cross-linking graphene and attaching it to polyamide resin PA6. The specific steps are as follows: polyamide PA6 resin and graphene oxide are mixed evenly in a ratio of 3:1, and placed in a ball mill. In a liquid nitrogen atmosphere, the two are subjected to a ball milling process, and the mixed powder obtained after ball milling is mixed evenly with a compatibilizer, a cross-linking agent, an antioxidant, and a lubricant in a ratio of 96:3:0.2:0.4:0.4 using a high-speed mixer, and the mixture is placed in a twin-screw extruder for extrusion and granulation to obtain the graphene oxide masterbatch. The processing temperatures of the extruder are 210°C, 230°C, 240°C, 240°C, 230°C, 230°C, 230°C, 220°C, 230°C, 240°C, and the screw speed is 400r / min.
[0034] The graphene oxide particle size D50≤5um;
[0035] The compatibilizer is at least one of POE-g-MAH, SEBS-g-MAH, and PP-g-MAH;
[0036] The cross-linking agent is at least one of dipropylbenzene peroxide, di-tert-butyl peroxide and tert-butyl perbenzoate;
[0037] The antioxidant is a mixture of a main antioxidant and an auxiliary antioxidant in a ratio of 1 / 2, wherein the main antioxidant is a hindered phenol antioxidant 1098 and the auxiliary antioxidant is a phosphite antioxidant 9228;
[0038] The lubricant is one or more of OP wax, polyester wax, and ethylene-acrylic acid copolymer.
[0039] The following examples are used to illustrate the preparation process of the high-strength long glass fiber reinforced polyamide composite material, wherein the parts mentioned in the examples and comparative examples are parts. In addition, the raw materials and reagents used in the examples and comparative examples of the present invention are conventionally purchased raw materials and reagents, which are as follows:
[0040] Polyamide PA6: viscosity 2.4, brand BE3250, Jiangsu Hongsheng;
[0041] High modulus alkali-free glass fiber uses continuous glass fiber: linear density 2400tex, brand SE4595, Owens Corning;
[0042] Compatibilizer: POE-g-MAH, brand CMG5805-L, Jiayirong;
[0043] Graphene oxide: brand NO-C-068-1, Shanghai Naio Nano Technology Co., Ltd.;
[0044] Cross-linking agent, dipropylbenzene peroxide (DCP), Akzo;
[0045] Chain extender masterbatch, brand name REGRANYL MB-25, Xingbeida Chemical;
[0046] Antioxidant 1098, BASF;
[0047] Antioxidant 9228, Dover, USA;
[0048] Lubricant, brand Licowax OP, Clariant;
[0049] Black masterbatch, brand BK-1032PAMB, Dongguan Zhichuangxin Materials Co., Ltd.
[0050] Example 1
[0051] The preparation process of high-strength long glass fiber reinforced polyamide composite material is as follows:
[0052] S1, preparation of graphene oxide masterbatch; polyamide PA6 resin and graphene oxide are mixed in a ratio of 2:1, and placed in a ball mill, and the two are subjected to ball milling process under liquid nitrogen atmosphere, and the mixed powder obtained after ball milling is mixed with a compatibilizer, a cross-linking agent, an antioxidant, and a lubricant in a ratio of 96:3:0.2:0.4:0.4 by a high-speed mixer, and the mixture is placed in a twin-screw extruder for extrusion and granulation to obtain graphene oxide masterbatch; wherein the processing temperatures of the extruder are 210°C, 230°C, 240°C, 240°C, 230°C, 230°C, 230°C, 220°C, 230°C, 240°C, and the screw speed is 400r / min.
[0053] S2, 54.5 parts of polyamide resin, 30 parts of high modulus alkali-free glass fiber, 10 parts of graphene oxide masterbatch, 1 part of compatibilizer, 0.2 parts of antioxidant 1010, 0.3 parts of antioxidant 9228, 0.2 parts of lubricant and 0.8 parts of black masterbatch are added to a stirring pot and mixed evenly, and then placed at the discharge port of a twin-screw extruder, and 3 parts of chain extender masterbatch are added from the side feeding port. After the material is sheared and plasticized by the twin screw, it is injection molded into an LFT-G impregnation mold at a constant conveying rate. The high modulus alkali-free glass fiber passes through the surface coating resin from the impregnation mold, and is finally cooled in a water tank, air-dried, and pelletized to obtain a high-strength long glass fiber reinforced polyamide composite material. The temperature of the impregnation mold is 300°C; the temperatures of the twin-screw extruder from zone 1 to zone 10 are 210°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 290°C, 290°C, and the screw speed is 400r / min.
[0054] Example 2
[0055] The preparation process of high-strength long glass fiber reinforced polyamide composite material is as follows:
[0056] S1, preparation of graphene oxide masterbatch; polyamide PA6 resin and graphene oxide are mixed in a ratio of 2:1, and placed in a ball mill, and the two are subjected to ball milling process under liquid nitrogen atmosphere, and the mixed powder obtained after ball milling is mixed with a compatibilizer, a cross-linking agent, an antioxidant, and a lubricant in a ratio of 96:3:0.2:0.4:0.4 by a high-speed mixer, and the mixture is placed in a twin-screw extruder for extrusion and granulation to obtain graphene oxide masterbatch; wherein the processing temperatures of the extruder are 210°C, 230°C, 240°C, 240°C, 230°C, 230°C, 230°C, 220°C, 230°C, 240°C, and the screw speed is 400r / min.
[0057] S2, add 47.5 parts of polyamide resin, 40 parts of high modulus alkali-free glass fiber, 8 parts of graphene oxide masterbatch, 2 parts of compatibilizer, 0.2 parts of antioxidant 1010, and 0.3 parts of antioxidant 9228 into a stirring pot and mix evenly, then place it at the discharge port of a twin-screw extruder, add 2 parts of chain extender masterbatch from the side feeding port, and after the material is sheared and plasticized by the twin screw, it is injection molded into the LFT-G impregnation mold at a constant conveying rate. The high modulus alkali-free glass fiber passes through the surface coating resin from the impregnation mold, and is finally cooled in a water tank, air-dried, and pelletized to obtain a high-strength long glass fiber reinforced polyamide composite material. The temperature of the impregnation mold is 300°C; the temperatures of the twin-screw extruder from zone 1 to zone 10 are 210°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 290°C, 290°C, and the screw speed is 400r / min.
[0058] Example 3
[0059] The preparation process of high-strength long glass fiber reinforced polyamide composite material is as follows:
[0060] S1, preparation of graphene oxide masterbatch; polyamide PA6 resin and graphene oxide are mixed in a ratio of 2:1, and placed in a ball mill, and the two are subjected to ball milling process under liquid nitrogen atmosphere, and the mixed powder obtained after ball milling is mixed with a compatibilizer, a cross-linking agent, an antioxidant, and a lubricant in a ratio of 96:3:0.2:0.4:0.4 by a high-speed mixer, and the mixture is placed in a twin-screw extruder for extrusion and granulation to obtain graphene oxide masterbatch; wherein the processing temperatures of the extruder are 210°C, 230°C, 240°C, 240°C, 230°C, 230°C, 230°C, 220°C, 230°C, 240°C, and the screw speed is 400r / min.
[0061] S2, 38 parts of polyamide resin, 50 parts of high modulus alkali-free glass fiber, 6 parts of graphene oxide masterbatch, 3 parts of compatibilizer, 0.2 parts of antioxidant 1010, 0.3 parts of antioxidant 9228, 0.5 parts of lubricant and 1 part of black masterbatch are added to a stirring pot and mixed evenly, and then placed at the discharge port of a twin-screw extruder, and 1 part of chain extender masterbatch is added from the side feeding port. After the material is sheared and plasticized by the twin screw, it is injection molded into an LFT-G impregnation mold at a constant conveying rate. The high modulus alkali-free glass fiber passes through the surface coating resin from the impregnation mold, and is finally cooled in a water tank, air-dried, and pelletized to obtain a high-strength long glass fiber reinforced polyamide composite material. The temperature of the impregnation mold is 300°C; the temperatures of the twin-screw extruder from zone 1 to zone 10 are 210°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 290°C, 290°C, and the screw speed is 400r / min.
[0062] Example 4
[0063] The preparation process of high-strength long glass fiber reinforced polyamide composite material is as follows:
[0064] S1, preparation of graphene oxide masterbatch; polyamide PA6 resin and graphene oxide are mixed in a ratio of 2:1, and placed in a ball mill, and the two are subjected to ball milling process under liquid nitrogen atmosphere, and the mixed powder obtained after ball milling is mixed with a compatibilizer, a cross-linking agent, an antioxidant, and a lubricant in a ratio of 96:3:0.2:0.4:0.4 by a high-speed mixer, and the mixture is placed in a twin-screw extruder for extrusion and granulation to obtain graphene oxide masterbatch; wherein the processing temperatures of the extruder are 210°C, 230°C, 240°C, 240°C, 230°C, 230°C, 230°C, 220°C, 230°C, 240°C, and the screw speed is 400r / min.
[0065] S2, 31 parts of polyamide resin, 60 parts of high modulus alkali-free glass fiber, 4 parts of graphene oxide masterbatch, 3 parts of compatibilizer, 0.2 parts of antioxidant 1010, 0.3 parts of antioxidant 9228, 0.2 parts of lubricant and 0.8 parts of black masterbatch are added to a stirring pot and mixed evenly, and then placed at the discharge port of a twin-screw extruder, and 0.5 parts of chain extender masterbatch are added from the side feeding port. After the material is sheared and plasticized by the twin screw, it is injection molded into an LFT-G impregnation mold at a constant conveying rate. The high modulus alkali-free glass fiber passes through the surface coating resin from the impregnation mold, and is finally cooled in a water tank, air-dried, and pelletized to obtain a high-strength long glass fiber reinforced polyamide composite material. The temperature of the impregnation mold is 300°C; the temperatures of the twin-screw extruder from zone 1 to zone 10 are 210°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 290°C, 290°C, and the screw speed is 400r / min.
[0066] Comparative Example 1
[0067] The preparation process of polyamide composite materials is as follows:
[0068] 62 parts of polyamide resin, 30 parts of high modulus alkali-free glass fiber, 2.5 parts of graphene oxide, 1 part of compatibilizer, 0.2 parts of antioxidant 1010, 0.3 parts of antioxidant 9228, 0.2 parts of lubricant and 0.8 parts of black masterbatch were added to a stirring pot and mixed evenly, then placed at the discharge port of a twin-screw extruder, and 3 parts of chain extender masterbatch were added from the side feeding port. After the material was sheared and plasticized by the twin screw, it was injection molded into an LFT-G impregnation mold at a constant conveying rate. The high modulus alkali-free glass fiber passed through the surface coating resin from the impregnation mold, and was finally cooled in a water tank, air-dried, and pelletized to obtain a high-strength long glass fiber reinforced polyamide composite material. The temperature of the impregnation mold is 300°C; the temperatures of the twin-screw extruder from zone 1 to zone 10 are 210°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 290°C, 290°C, and the screw speed is 400r / min.
[0069] Comparative Example 2
[0070] The preparation process of polyamide composite materials is as follows:
[0071] S1, preparing graphene oxide masterbatch according to step S1 of Example 1;
[0072] S2, adding 57.5 parts of polyamide resin, 30 parts of high modulus alkali-free glass fiber, 10 parts of graphene oxide masterbatch, 1 part of compatibilizer, 0.2 parts of antioxidant 1010, 0.3 parts of antioxidant 9228, 0.2 parts of lubricant and 0.8 parts of masterbatch into a stirring pot and mixing evenly, and then placing the material at the discharge port of a twin-screw extruder. After the material is sheared and plasticized by the twin screw, it is injection molded into an LFT-G impregnation mold at a constant conveying rate. The high modulus alkali-free glass fiber passes through the surface coating resin from the impregnation mold, and is finally cooled in a water tank, air-dried, and pelletized to obtain a high-strength long glass fiber reinforced polyamide composite material. The temperature of the impregnation mold is 300°C; the temperatures of the twin-screw extruder from zone 1 to zone 10 are 210°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 290°C, 290°C, and the screw speed is 400r / min.
[0073] The amounts of raw materials used in Examples 1-4 and Comparative Examples 1-2 are shown in Table 1 below:
[0074] Table 1 Raw material dosage of Examples 1-4 and Comparative Examples 1-2
[0075] Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 PA6 54.5 47.5 38 31 62 57.5 Continuous glass fiber 30 40 50 60 30 30 Graphene oxide masterbatch 10 8 6 4 / 10 Graphene oxide / / / / 2.5 / Compatibilizer 1 2 3 3 1 1 Chain Extender Masterbatch 3 2 1 0.5 3 / Antioxidant 1098 0.2 0.2 0.2 0.2 0.2 0.2 Antioxidant 9228 0.3 0.3 0.3 0.3 0.3 0.3 Lubricants 0.2 / 0.5 0.2 0.2 0.2 color masterbatch 0.8 / 1 0.8 0.8 0.8
[0076] The materials prepared in Examples 1-4 and Comparative Examples 1-2 were subjected to performance tests, and the test standards and test data are shown in Table 2 below;
[0077] Table 2 Test results of material properties prepared in Examples 1-4 and Comparative Examples 1-2
[0078]
[0079]
[0080] The graphene oxide masterbatch prepared in Examples 1-4 is blended and modified with a polyamide resin to prepare a high-strength long glass fiber reinforced polyamide composite material; polyamide PA6 resin and graphene oxide are selected and mixed in proportion and then placed in a ball mill, and the two are subjected to a ball milling process in a liquid nitrogen atmosphere to obtain a mixed powder, and the obtained mixed powder is mixed evenly with a compatibilizer, a cross-linking agent, an antioxidant, and a lubricant at a high speed and then placed in a twin-screw extruder for extrusion granulation to obtain a graphene oxide masterbatch. The graphene oxide masterbatch prepared in this way not only fully solves the dispersion problem of graphene oxide, but also, under the action of the cross-linking agent, the nylon molecular chain and the hydroxyl groups on the surface of the graphene are cross-linked and bonded, and the nylon molecules are effectively grafted onto the graphene sheet layer. The synergistic reinforcement effect of graphene and glass fiber greatly improves the mechanical properties of the long glass fiber reinforced polyamide composite material, and also gives the composite material good conductivity.
[0081] From the results in Table 2, it can be seen that the introduction of graphene oxide significantly improves the mechanical properties of the long glass fiber reinforced polyamide composite material, and effectively reduces the resistance and improves its conductivity. Referring to Example 1 and Comparative Example 1, it can be clearly observed that when graphene oxide is directly added to the composite material system, the mechanical properties of the prepared composite material generally show a significant decline, and the volume resistivity is significantly higher. This is because the graphene oxide fails to be fully dispersed in the resin system, thereby exerting its benefits. Referring to Example 1 and Comparative Example 2, it can be observed that when the chain extender masterbatch is not added to the system, the mechanical properties of the obtained composite material are low. This is because the addition of the chain extender can, on the one hand, react with the functional groups on the polymer chain to extend the molecular chain, increase the molecular weight, increase the entanglement between the chains, and make it difficult for the molecular chain to slip, thereby improving the mechanical properties; on the other hand, it can make the PA6 molecules grafted on the surface of the graphene oxide more closely combined with the glass fiber during the chain extension process, and the graphene oxide is evenly attached to the surface of the continuous glass fiber, thereby further effectively improving the mechanical properties of the composite material.
[0082] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0083] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A polyamide composite material, characterized in that: Including the following raw materials by weight: The graphene oxide masterbatch is formed by cross-linking graphene oxide and attaching it to polyamide resin PA6.
2. A polyamide material according to claim 1, characterized in that: The polyamide resin is one or more of the aliphatic polyamide resins PA6, PA46, PA56, PA66, PA11, PA12, PA610, PA1010, PA1012, PA612, and PA1212.
3. A polyamide composite material according to claim 1, characterized in that: The monofilament diameter of the high modulus alkali-free glass fiber is 15-20 um, and the linear density is 1200 tex, 2400 tex or 3600 tex.
4. A polyamide composite material according to claim 1, characterized in that: The chain extender masterbatch is an epoxy chain extender.
5. A polyamide composite material according to claim 1, characterized in that: The processing aid is at least one of an antioxidant, a weathering agent, a lubricant and a pigment.
6. A polyamide composite material according to claim 1, characterized in that: The preparation steps of the graphene oxide masterbatch are as follows: Step 1: Take polyamide PA6 resin and graphene oxide in a ratio of 3:1, mix them evenly, put them in a ball mill, and perform ball milling process on the two in a liquid nitrogen atmosphere to obtain a mixed powder; Step 2: Mix the powder with the compatibilizer, cross-linking agent, antioxidant and lubricant in a ratio of 96:3:0.2:0.4:0.4, mix them evenly at high speed using a high-speed mixer, and extrude and granulate them in a twin-screw extruder to obtain graphene oxide masterbatch.
7. A polyamide composite material according to claim 6, characterized in that: The graphene oxide particle size D50≤5um; the cross-linking agent is at least one of dipropylbenzene peroxide, di-tert-butyl peroxide and tert-butyl perbenzoate.
8. A polyamide composite material according to claim 5 or 7, characterized in that: The compatibilizer is at least one of POE-g-MAH, SEBS-g-MAH, and PP-g-MAH; the antioxidant is a mixture of a main antioxidant and an auxiliary antioxidant in a ratio of 1 / 2, the main antioxidant is a hindered phenol antioxidant 1098, and the auxiliary antioxidant is a phosphite antioxidant 9228; the lubricant is one or more of OP wax, polyester wax, and ethylene-acrylic acid copolymer.
9. A method for preparing a polyamide composite material according to any one of claims 1 to 8, characterized in that: The following steps are involved: Add polyamide resin, high modulus alkali-free glass fiber, graphene oxide masterbatch, compatibilizer and other processing aids into a stirring pot and mix evenly, then place it at the discharge port of a twin-screw extruder, add the chain extender masterbatch from the side feeding port, and after the material is sheared and plasticized by the twin screw, it is injected into the LFT-G impregnation mold at a constant conveying rate. The high modulus alkali-free glass fiber passes through the surface coating resin from the impregnation mold, and is cooled in a water tank, air-dried, and pelletized to obtain a polyamide composite material.
10. Use of a polyamide composite material according to any one of claims 1 to 8 in the preparation of automotive plastic parts.
Citation Information
Patent Citations
Preparation method of graphene oxide and polyamide nanocomposite material with high barrier property
CN106009640A
Preparation method for antistatic graphene nylon 6 composite material
CN109180929A
Preparation method of high-performance carbon fiber / graphene nylon 6 composite material
CN109251518A
High-strength and high-toughness carbon fiber / graphene nylon 6 composite material preparation method
CN109265985A
Preparation method of high-strength and high-modulus long glass fiber reinforced polyamide composite material
CN117866427A
Cited By
High-heat-resistance injection molding composite material for electronic component and preparation method thereof
CN121249141A
Preparation method of high-strength polypropylene / polyamide 6 / glass fiber composite material
CN121628244A
High-thermal-conductivity low-resistance epoxy adhesive solution, preparation method and use thereof
CN122772330A